The Effectiveness of Problem Based Learning Integrated with Local Wisdom in Enhancing Students’ Scientific Literacy: A Systematic Literature Review - Hikmah Cahya Utami; Yuni Sri Rahayu; Sifak Indana (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the effectiveness of implementing Problem Based Learning (PBL) integrated with local wisdom in improving students’ scientific literacy in science and biology learning. Studies examining the integration of PBL and local wisdom in relation to scientific literacy remain limited; therefore, this research was conducted to provide a comprehensive overview of research trends and their impact on learning. This study employed a Systematic Literature Review (SLR) method following the PRISMA guidelines. Data were collected through article searches in the Google Scholar, DOAJ, Portal Garuda/SINTA, and Scopus databases, covering publications from 2020 to 2025. Based on the processes of identification, screening, and selection, 45 articles met the inclusion criteria. The data were analyzed qualitatively and strengthened through bibliometric mapping using VOSviewer. The findings indicate that the implementation of PBL integrated with local wisdom is effective in improving students’ scientific literacy through investigation activities, problem-solving, and discussions based on local contextual phenomena. The most frequently studied topics include ecology, interactions between living organisms and their environment, and biotechnology. Bibliometric analysis also revealed a strong relationship among the keywords “PBL,” “local wisdom,” and “scientific literacy.” These findings contribute to the development of contextual, meaningful, and relevant science learning that aligns with students’ daily lives.